2010
DOI: 10.1093/nar/gkq853
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent xDNA nucleotides as efficient substrates for a template-independent polymerase

Abstract: Template independent polymerases, and terminal deoxynucleotidyl transferase (TdT) in particular, have been widely used in enzymatic labeling of DNA 3′-ends, yielding fluorescently-labeled polymers. The majority of fluorescent nucleotides used as TdT substrates contain tethered fluorophores attached to a natural nucleotide, and can be hindered by undesired fluorescence characteristics such as self-quenching. We previously documented the inherent fluorescence of a set of four benzo-expanded deoxynucleoside analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 59 publications
(55 reference statements)
1
39
0
Order By: Relevance
“…87 More recently, the TdT enzyme has also been used to incorporate benzo-expanded deoxynucleoside analogs, dxATP and dxCTP, forming fluorescent homopolymers. 263 …”
Section: Methods Of Assembling Dna Multichromophoresmentioning
confidence: 99%
“…87 More recently, the TdT enzyme has also been used to incorporate benzo-expanded deoxynucleoside analogs, dxATP and dxCTP, forming fluorescent homopolymers. 263 …”
Section: Methods Of Assembling Dna Multichromophoresmentioning
confidence: 99%
“…Size-expanded dxNTPs, which contain a benzene ring within the base moiety of each nucleoside (Figure 1A), were synthesized as described (19). These expanded nucleosides form canonical base pairs and increase the width of double-stranded DNA by 2.4 Å (14).…”
Section: Resultsmentioning
confidence: 99%
“…The large nucleobase is likely to induce steric hindrance within the active site of DNA polymerases, which may prevent proper positioning of the nucleotide near the 3′-hydroxyl at the primer terminus for the phosphodiester transfer reaction. Interestingly, previous studies have shown efficient utilization of dxNMPs by terminal deoxynucleotidyl transferase, which unlike common DNA polymerases does not require a template for the nucleotidyl transfer, thus potentially explaining its ability to accommodate large unnatural nucleotides (19). …”
Section: Introductionmentioning
confidence: 99%
“…133 (A, B) Spectra of xDNTP monomers (purple, red) and of TdT reaction products (green, blue). (A) Incorporation of dxATP; (B) incorporation of dxCTP.…”
Section: Figmentioning
confidence: 99%
“…(C) dxATP without TdT; (D) dxATP with TdT; (E) dxCTP without TdT; (F) dxCTP with TdT. 133 Reprinted from ref. 133 by permission of Oxford University Press, Copyright 2010.…”
Section: Figmentioning
confidence: 99%